Penggunaan Sistem Barcode dalam Memudahkan Pemantauan pada Inspeksi Alat Pemadam Api Ringan (APAR) - Dery Riwayanto; Abdul Hakim Zakkiy Fasya (Yayasan Literasi Sains Indonesia, 2023)
Fire, as a universal catastrophic phenomenon, presents the potential for significant losses to people, assets, and productivity around the world. Therefore, an efficient set of preventive and responsive measures is needed to reduce the risk of fire. In Indonesia, one approach in overcoming the threat of fire is through the use of Light Fire Extinguishers (APAR). The Head Office of PT X, a company located in a 23-storey building, faces challenges in conducting routine inspections of fire extinguishers. This obstacle arises due to the large number of fire extinguishers (84 units) and the limited number of HSSE (Health, Safety, Security, and Environment) staff. In order to overcome this problem, designing a barcode-based fire extinguisher inspection checklist connected to a spreadsheet is a relevant solution. The goal is to ensure that each fire extinguisher is ready to be used to extinguish fires. The fire extinguisher inspection data is processed and recorded in a database in a spreadsheet. Based on the results of the study, the barcode-based fire extinguisher inspection checklist system connected to this spreadsheet involves three levels of users, namely the operator responsible for conducting inspections, supervisors who have the authority to provide validation of inspection results, and admins who are in charge of managing and adding fire extinguisher inspection data that has been carried out.